Implementasi Surat Menyurat Dalam Sistem Informasi Desa Berbasis Web Di Desa Jantiganggong - Izzatul Umami; Firdaus Arya Ramadhan; Winarti Winarti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Along with the times, public services related to the management of correspondence and recording need to be carried out properly. Therefore, technological developments make it easier to manage community mobility documents in the village or district. The development of this technology is in the form of a website that can be accessed online to facilitate correspondence activities. However, until now there are still several villages that have not used the development of website technology for correspondence, one of which is Jantiganggong Village. The purpose of this research is to implement a web-based information system related to correspondence, the method used is the waterfall. The results showed that the existence of an online correspondence system could make the process of making letters easier and also provide convenience for the people of Jantiganggong Village in submitting various applications.